Novel molecular trends in the management of advanced non-small-cell lung cancer. Issue 6 (June 2012) - Metro, Giulio; Crinò, Lucio
In this article, we will summarize some of the aspects covered by key opinion leaders at the Perspectives in Lung Cancer Congress, particularly focusing on the most recent molecular discoveries in non-small-cell lung cancer which, we believe, will have a deep impact on the clinical development of novel targeted therapies in the future. We discuss genetic alterations in squamous cell carcinoma, crizotinib therapy for ALK-positive tumors, the latest information on antiangiogenic therapies, and strategies aimed at interfering with the Ras–Raf–MEK pathway in more detail. A special emphasis is placed on the potential implications that each covered point will have for the management of advanced non-small-cell lung cancer.